Podpora výuĉby PLC systémov na vysokých školách v SR - LUKÁĈOVÁ, DANKA; BÁNESZ, GABRIEL (Journal of Education, Technology and Computer Science, 2017)
Study programs oriented on teacher preparation at universities respond to the needs of the labor market and include subjects in their study programs where students are acquainted with new materials and technologies of the industrial practice. PLC industrial control systems are one of these technologies. The Department of Technology and Information Technologies at the Faculty of Pedagogy of UKF in Nitra included four subjects in its study programs, which provide students some basic knowledge about PLC systems. To increase the interest of students in this subject, they decided to create remote laboratories that can be used by students in a distance form of study, as well as within contact hours during exercises. To create remote laboratories for pneumatic and hydraulic systems will be used hardware elements using the PLC together with a web interface for remote access and direct approach, methodology and educational materials suitable for inclusion in the educational process. Remote access to laboratories along with contact teaching allows the user to gain new knowledge in the field of pneumatic and hydraulic systems. The present proposal will by its outputs contribute to increasing competencies of teachers of technical subjects in this area.